Metafory odzwierzęce w funkcji predykatu w języku polskim, rosyjskim i angielskim - Czapiga, Artur (Przegląd Rusycystyczny, 2006)
ZOOMORPHICAL METAPHORS DENOTING HUMAN BEINGSIN POLISH, RUSSIAN AND ENGLISH Summary The article discusses sentences containing zoomorphical metaphors denoting human beings inpredicate function in Polish, Russian and English. The sentences are of a type "Jesteś świnia (-ą), "Ты свинья", "You are apig". The metaphor-predicate ascribes the subject (hidden or expressedby a€noun or a€pronoun) with some non-typical feature. It occurs to be a€very important way oftransmitting subjective evaluation of a€human being it denotes.